2013
DOI: 10.1175/mwr-d-12-00303.1
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Seventh-Order Amplitude Accuracy in Leapfrog Integrations

Abstract: The leapfrog time-stepping scheme is commonly used in general circulation models of weather and climate. The Robert-Asselin filter is used in conjunction with it, to damp the computational mode. Although the leapfrog scheme makes no amplitude errors when integrating linear oscillations, the Robert-Asselin filter introduces first-order amplitude errors. The RAW filter, which was recently proposed as an improvement, eliminates the first-order amplitude errors and yields third-order amplitude accuracy. This devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…). For example, there have been recent developments in stabilizing the computational mode of the commonly used leapfrog time‐stepping scheme using the Robert–Asselin–Williams (RAW) filter (Williams, ; ; ). Specifically, the use of the RAW filter, instead of the Robert–Asselin filter, reduces biases in the location of the Gulf Stream (Young et al.…”
Section: Introductionmentioning
confidence: 99%
“…). For example, there have been recent developments in stabilizing the computational mode of the commonly used leapfrog time‐stepping scheme using the Robert–Asselin–Williams (RAW) filter (Williams, ; ; ). Specifically, the use of the RAW filter, instead of the Robert–Asselin filter, reduces biases in the location of the Gulf Stream (Young et al.…”
Section: Introductionmentioning
confidence: 99%
“…Following Williams (), let us now assume that in a computational code both x ( t ) and are kept in memory. Then we can use a linear combination of them to calculate the tendency associated with the slow term, which we write as .…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Amezcua et al () have found that the RAW filter improves the skill of medium‐range weather forecasts compared with the Robert–Asselin filter. Many current models have subsequently adopted the RAW filter in place of the Robert–Asselin filter (see Williams, for a list).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations